Synthesis of EVA-g-PLA copolymers using transesterification reactions - Moura, I. (2012)
The synthesis of EVA-g-PLA grafted copolymers was carried out by reactive extrusion, through transesterification reaction between ethylene vinyl acetate copolymer (EVA) and polylactide (PLA), using titanium propoxide (Ti(OPr)4) and titanium phenoxide (Ti(OPh)4) as catalysts. Different materials were prepared by changing the relative amount of polylactide and catalyst. The extent of the grafting reaction, which depends on the quantity of polylactide and catalysts, was estimated by selective extractions. The influence of the same parameters on the final structure, morphology and thermal and mechanical properties was also evaluated. The results showed that Ti(OPr)4 exhibited higher efficiency as a catalyst than Ti(OPh)4. Moreover, using the former catalyst, 25 wt.% of EVA-g-PLA copolymer was synthesized. The sample containing the higher amount of copolymer exhibits the better properties and the higher biodegradability.